Use of Sustainable Energy Systems in Educational Institutions - John Vourdoubas (Engineering And Technology Journal, 2024)
Educational institutions like other public and private organizations should try to eliminate their carbon footprint for the achievement of the ambitious 2050 target of net-zero carbon emissions. Several mature, reliable and cost-effective sustainable energy technologies can be used in these institutions replacing the use of fossil fuels and reducing their carbon emissions. Solar energy, wind energy and biomass can be used for heat and electricity generation replacing the use of oil, gas and grid electricity. Additionally, various low-carbon emission technologies including heat pumps, co-generation systems, fuel cells, district heating systems and power storage technologies can be also used in them. The combined use of these technologies in schools, colleges and universities can replace the current use of conventional energy sources reducing or completely eliminating their carbon emissions. The abovementioned benign energy technologies are already used commercially in several sectors proving their reliability and cost-effectiveness. It has been indicated that a plethora of green energy technologies can be used in educational institutions eliminating their carbon footprint achieving the desired global 2050 target of net-zero carbon emissions. Our results could be useful to policy makers and to the authorities of schools, colleges and universities who are willing to promote their environmental sustainability, achieving economic benefits and offering valuable educational opportunities to students.